The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2000
DOI: 10.4049/jimmunol.164.10.5023
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: The Tumor Counterattack Hypothesis Revisited: Colon Cancer Cells Do Not Induce T Cell Apoptosis Via the Fas (CD95, APO-1) Pathway

Abstract: The counterattack hypothesis, suggesting that cancer cells express Fas ligand (FasL) and are able to kill Fas-expressing tumor-infiltrating activated T cells, was supported by reports of the killing of Jurkat cells by FasL-expressing human colon cancer cell lines. Through the use of an improved cytotoxic assay in which soluble FasL and FasL-transfected KFL9 cells were used as positive controls, we show that none of seven human colon cancer cell lines induce apoptosis of two Fas-expressing target cell lines, Ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
1

Year Published

2001
2001
2004
2004

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(43 citation statements)
references
References 24 publications
2
38
1
Order By: Relevance
“…The T lymphocytes underwent apoptosis following coculture with FasL-expressing rat hippocampal neurons, but only a minority of the T lymphocytes were rescued by inhibiting the Fas-FasL interaction with Abs (18). Other work showed that several T cell lines do not undergo apoptosis after confrontation with FasL-expressing tumors or APCs (22,23), also suggesting a distinct mechanism for the FasL-dependent immunodeviation observed in vivo (21).…”
Section: Discussionmentioning
confidence: 97%
“…The T lymphocytes underwent apoptosis following coculture with FasL-expressing rat hippocampal neurons, but only a minority of the T lymphocytes were rescued by inhibiting the Fas-FasL interaction with Abs (18). Other work showed that several T cell lines do not undergo apoptosis after confrontation with FasL-expressing tumors or APCs (22,23), also suggesting a distinct mechanism for the FasL-dependent immunodeviation observed in vivo (21).…”
Section: Discussionmentioning
confidence: 97%
“…20,36 Fas-L detection on some tumor samples has suffered from technical inconsistencies based on unspecific Abs, 28,37 and the lack of Fas-L detection using FACS or RT ± PCR. 21,35,38 We demonstrated Fas-L expression on escape tumor cell lines by FACS analysis, thus avoiding lymphocyte contamination that may contribute to Fas-L detection in fresh tumor samples, by immunohistochemistry using a different antibody both on cytospins and on tumor samples after reinjection in vivo and by RT ± PCR using specific primers and sequencing of the resulting fragment.…”
Section: Discussionmentioning
confidence: 99%
“…The 002 hybridoma or D10 Th2 cells were used as killer cells. The targets were A20 mouse B cells or Jurkat human T cells, which constitutively express the Fas receptor and are capable of undergoing Fas-mediated cell death (28,29). To measure the amount of fragmented DNA produced by the target cells but not the killer cells, target cells were labeled with [ 3 H]thymidine.…”
Section: Ciita-expressing Cells Have Reduced Killing Abilitymentioning
confidence: 99%